Las estrategias metodológicas aplicadas por los docentes, en las prácticas de laboratorio y su relación en los aprendizajes significativos del área de ciencias naturales de los niños y niñas del sexto año de educación general básica de la escuela fiscal mixta “25 de Junio” de la parroquia Lourdes, cantón Paltas, provincia de loja, año académico 2012 - 2013”. Lineamientos propositivos - Condoy Curimilma, Martha Elizabeth (2014)
The present investigation work makes reference to: "THE APPLIED METHODOLOGICAL STRATEGIES FOR THE EDUCATIONAL ones, IN THE PRACTICES OF LABORATORY AND THEIR RELATIONSHIP IN THE SIGNIFICANT LEARNINGS OF THE AREA OF NATURAL SCIENCES OF THE CHILDREN AND GIRLS OF THE SIXTH YEAR OF BASIC GENERAL EDUCATION OF THE MIXED FISCAL SCHOOL JUNE OF THE PARISH 25 LOURDES, CANTON AVOCADOS, COUNTY DE LOJA, ACADEMIC YEAR 2012 - 2013". LIMITS PROPOSITIVOS, had as general purpose to identify the Methodological Strategies for the teaching and the significant learning that use of today in day the educational ones to develop the dexterities, the students' abilities. In the development of the investigation it was necessary the use of the following methods: the scientist, inductive-deductive, analytic-synthetic, descriptive, bibliographical, was also used the such techniques as: the survey, questionnaire applied to the investigated community (educational and students) and the observation like guide; the same one that you/they were good to obtain truthful and objective information, being a fundamental support in emitting adjusted approaches to the existent problem in the educational institution. As product of the carried out field investigation the rejection of, the first hypothesis settled down making stress in that the educational ones yes they apply the strategies for the teaching and the significant learning of the Area of Natural Sciences just as he/she suggests the current Curriculum inside the pedagogic process, based on the second hypothesis it doesn't allow them potencies the development of the Methodological Strategies in the laboratory practices because an equipped laboratory doesn't exist what doesn't facilitate a teaching-learning process. It is of vital importance to motivate directive and educational to be qualified, to foment the autoformación through the investigation of other texts, or the technologies knowing the changes and innovations that are given in the educational field, selecting the new methodologies that adapt to the educational reality, contributing to the improvement of the educational quality. For what is recommended to Plan shops of school coexistences, to strengthen the interrelations inside the institution, this will benefit the students since he/she will help them to be more aware of what happens inside the school context.